Music Familiarity Affects EEG Entrainment When Little Attention Is Paid - Kumagai, Yuiko; Matsui, Ryosuke; Tanaka, Toshihisa (Frontiers in Human Neuroscience, 2018)
To investigate the brain’s response to music, many researchers have examined cortical entrainment in relation to periodic tunes, periodic beats, and music. Music familiarity is another factor that affects cortical entrainment, and electroencephalogram (EEG) studies have shown that stronger entrainment occurs while listening to unfamiliar music than while listening to familiar music. In the present study, we hypothesized that not only the level of familiarity but also the level of attention affects the level of entrainment. We analyzed an EEG while participants either listened to music or watched a silent movie in order to investigate whether cortical entrainment is related to attention and music familiarity. The cross-correlation function averaged across channels, trials, and participants exhibited a pronounced positive peak at time lags around 130 ms and a negative peak at time lags around 260 ms. The statistical analysis of the two peaks revealed that the level of attention did not affect the level of entrainment, and moreover, that even when little attention is given, the entrainment level when listening to unfamiliar music is stronger than that when listening to familiar music. This may indicate that the familiarity of music affects cortical activities when attention is not fully devoted to listening to music.